Novel immunotherapy combinations in clinical trials for hepatocellular carcinoma: will they shape the future treatment landscape - DEMİRTAŞ, COŞKUN ÖZER (My University, 2022)
Introduction Underlying liver disease and the intrinsic chemoresistance have historically hampered the development of efficacious treatments in HCC. However, in the last few years, immunotherapy-based combinations have emerged as efficacious therapeutic strategy in this setting. This paper critically summarizes the recent therapeutic progress in the systemic treatment of HCC. Area covered This paper examines the preclinical rationale of the following combinations in HCC: dual checkpoint inhibitors, immune checkpoint inhibitors plus anti-angiogenic agents, and immune checkpoint inhibitors plus tyrosine kinase inhibitors. Results of recent clinical studies are presented, along with a brief overview of ongoing and future trials. Expert opinion The approval of atezolizumab plus bevacizumab and the positive results of the HIMALAYA trial have broadened the therapeutic scenario for advanced HCC, opening, at the same time, new challenges. First of all, predictive biomarkers to allocate patients to the best treatment are eagerly required; second, specific studies are urgently needed to define the use of new combinations in patients usually excluded from clinical trials, e.g. those with deranged liver function and HIV or transplant recipients. Finally, with new combinations being translated into earlier stages, profound changes are soon expected in the adjuvant and neoadjuvant setting.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Immunotherapy; HCC; systemic therapy; combinations; ATEZOLIZUMAB PLUS BEVACIZUMAB; OPEN-LABEL; DOUBLE-BLIND; PHASE-III; 1ST-LINE TREATMENT; SORAFENIB; TUMOR; TREMELIMUMAB; CABOZANTINIB; IMBRAVE150; Immunotherapy; HCC; systemic therapy; combinations